TRIPHENYLTIN (IV) GLUTARATES: SYNTHESIS, FT-IR AND MÖSSBAUER STUDIES - MOUHAMADOU SEMBENE BOYE; MOUHAMADOU BIRAME DIOP; MODOU SARR; AMINATA DIASSE-SARR; LIBASSE DIOP; ALAIN WATTIAUX (Journal of Engineering Studies and Research)
Four new adducts catena-O,O′-glutaratotriphenylstannate, [(Me4N)2O2C(CH2)3CO2×4SnPh3Cl] (1), [(Me4N)2O2C(CH2)3CO2×3SnPh3Cl] (2), [(SnPh3)2O2C(CH2)3CO2×SnPh3Cl] (2′) and [(Cy2NH2)2O2C(CH2)3CO2×SnPh3Cl] (3), have been isolated from the reactions carried out in solution. The compounds have been characterized by FT-IR and Mössbauer spectroscopies except for 2’ whose structure is proposed on the basis of FT-IR data. Overall, the spectra studies sheew existence of several caracteristic bands such as υ (C=O), υ (CO2–), υ (Sn–O), υ (Sn–Cl), vibrations of glutarate ions, and the intense doublet showing the presence of phenyl groups. In the solid state, the suggested structures are discrete or of infinite chain. In this work, the geometry at Sn centers, trigonal bipyramidal or tetrahedral, is ascertained by the Mössbauer parameters. The glutarate ions exhibit a monodentate, tridentate or tetradentate coordination behavior towards the Sn atoms.